Structuring Relations in Civil Law after the Termination of Relations between Subjects - DERGACHOV, Viktor S.; VASYLYEVA, Valentyna A.; KABAHA, Ali; GRIBINCEA, Alexandr A.; KOVACH, Denys L. (Journal of Advanced Research in Law and Economics; Vol 11 No 1 (2020): JARLE Volume XI Issue 1(47) Spring 2020, 2020)
The relevance of structuring relations in the field of civil law is determined by the forms of interaction between the subjects that were the initiators of the termination of legal relations. In this regard, the issues of maintaining relations, which could be continued in the future, are regulated on the basis of other contractual relations. With that, the works of legal scholars do not always provide sufficient grounds to propose points of fixation of the termination of relations. In this regard, the establishment of the meaning of legal facts for the formation of high-quality relationships between legal subjects after the termination of interaction remains very relevant. The novelty of the study is determined by the fact that for the first time the aspects of creating and consolidating forms that would ensure sustainable development and minimize conflicts after termination of contractual relations are considered in civil law. The authors of the paper analyze the current legislative provisions and determine the direction of its development in the context of globalization. The article explores the theoretical construct of these relations and provides an analysis of civil legislation as applied to industry standards of economic legislation. The practical significance of the study is determined by the fact that the application of the developed provisions will facilitate the harmonization of national legislations in the formation of bloc legal systems.